Caste, reservation, atrocity law and discrimination - Khora, Sthabir (London : Routledge, 2025)
This book is a collection of essays based on the thoughts generated by teaching courses and doing research related to the sociology of education and sociology of law over the years in TISS. It compiles theorizations, judgements, consequences, and ramifications to present a collection of free-thinking essays around the interrelated themes of caste, reservation, atrocity law, and discrimination. While it takes into account existing thinking on particular matters, it also reaches new junctures and presents them to the reader. Among other topics, this book also details the academic strategy for undermining caste, discusses the popular polemic around reservation, and explores the interface between criminal law and caste. The subject matter of this book also includes: Escape from Caste Through Conversion: Is there a Way Out or a Way In? Reservation and the Creamy Layer Principle: Solving the Puzzle Questioning Excellence: Expelling 73 Students in IIT Roorkee Lacking the Basics: The Supreme Court Judgement on Atrocities Act Law and Exclusion Print edition not for sale in South Asia (India, Sri Lanka, Nepal, Bangladesh, Pakistan or Bhutan)
Abbreviations and GlossaryPreface1. IntroductionPART I: CASTE2. Shastra (scripture) or Shastra (power) Origin of Caste: Sociological Imaginations3. Amartya Sen, Capability Approach and Caste4. Inter-Caste Marriage: Pain or Gain5. Escape from Caste Through Conversion: Is there a Way Out or a Way in?6. Sociology of Education: Towards Inclusive TheorisingPART II: RESERVATION7. Patel Agitation and the Rationale Behind SC/ST Reservations8. Reservation and the Creamy Layer Principle: Solving the Puzzle9. Creamy Layer: Jurisprudence in the Air10. Fifty per cent Ceiling on Reservation: Can Efficiency Override Justice?11. Questioning Excellence: Expelling 73 Students in IIT Roorkee12. Judicial Independence or Sovereignty!13. Reservation in Private Sector Employment: Is It Justified?PART III: LAW, ATROCITY AND DISCRIMINATION14. 'Final Reports' Under Section 498A and the SC/ST Atrocities Act15. Lacking the Basics: The Supreme Court Judgement on Atrocities Act16. Misconstruction of the Anti-Atrocities Act's Misuse17. Removing Discrimination in Universities18. Law and ExclusionIndex
Keywords: Caste -- India; Reverse discrimination -- India; Sociological jurisprudence -- India; Dalits -- Crimes against -- Law and legislation -- India; India -- Scheduled tribes -- Crimes against -- Law and legislation; SOCIAL SCIENCE / Sociology / General